Partial Purification and Characterization of Rhodanese from Rainbow Trout (Oncorhynchus mykiss) Liver. (2nd May 2012) - Tayefi-Nasrabadi, Hossein; Rahmani, Reza
Abstract : Cyanide is one of the most toxic substances present in a wide variety of food materials that are consumed by animals. Rhodanese, a ubiquitous enzyme, can catalyse the detoxification of cyanide by sulphuration reaction. In this study, rhodanese was partially purified and characterized from the liver tissue homogenate of the rainbow trout. The enzyme was active in a broad range of pH, from 5 to 12. The optimal activity was found at a high pH (pH 10.5), and the temperature optimum was 25 ∘ C. The enzyme was heat labile, losing > 50% of relative activity after only 5 min of incubation at 40 ∘ C. The K m values for KCN and Na2 S2 O3 as substrates were 36.81 mM and 19.84 mM, respectively. Studies on the enzyme with a number of cations showed that the activity of the enzyme was not affected by Sn 2+, but Hg 2+, Ba 2+, Pb 2+, and Ca 2+ inhibited and Cu 2+ activated the enzyme with a concentration-dependent manner.